Through the Looking Glass : Can Classroom Observation and Coaching Improve Teacher Performance in Brazil? - Bruns, Barbara (World Bank, Washington, DC, 2017)
This study conducted a randomized evaluation of a program in the Brazilian state of Ceara. The program was designed to improve teachers’ effectiveness by increasing their professional interaction and sharing of classroom practice. In 175 of 350 secondary schools, teachers were provided with benchmarked feedback from classroom observations and access to expert coaching. Schools’ uptake of the coaching program was high (85 percent). Over a single school year, the program increased teachers’ time on instruction and student engagement and produced statistically significant gains in student learning on the Ceara state assessment and the national secondary school exit exam. Controlling for individual students’ prior-year learning outcomes, schools exposed to the program had 0.05-0.09 standard deviation higher performance on the state test and 0.04-0.06 standard deviation higher scores on the national test. Implementation fidelity strongly boosted program impacts. In the 49 schools where the pedagogical coordinators achieved the highest certification at the end of the program, student scores were 0.13-0.23 standard deviation higher on the state test and 0.13-0.17 standard deviation higher on the national test. Coaching delivered by Skype kept the costs of the program low, $2.40 per student, and produced cost-effective impacts on learning in comparison with other rigorously evaluated teacher training interventions. The combination of classroom observation feedback and expert coaching appears to be a promising strategy for whole-school efforts to raise teacher effectiveness.